Cross-Sectional Associations Between Cardiac Biomarkers, Cognitive Performance, and Structural Brain Changes Are Modified by Age: The Maastricht Study. Issue 8 (August 2018) - Veugen, Marja G.J.; Henry, Ronald M.A.; Brunner-La Rocca, Hans-Peter; Dagnelie, Pieter C.; Schram, Miranda T.; van Agtmaal, Marnix J.M.; van der Kallen, Carla J.H.; Sep, Simone J.S.; van Boxtel, Martin P.J.; Bekers, Otto; Meex, Steven J.R.; Jansen, Jacobus F.A.; et al.
Abstract : Objective—: NT-proBNP (N-terminal pro-B-type natriuretic peptide) and cardiac troponin T (cTNT) are associated with cognitive performance. Whether this extends to individuals <60 years of age is unclear. We investigated whether age modified the associations between NT-proBNP and cTNT and cognitive performance and structural brain changes. Approach and Results—: In 3011 individuals (60±8 years; 49% women), NT-proBNP and cTNT, memory, information processing speed and executive functioning, grey matter (GM) and white matter, and white matter hyperintensity (WMH) volumes were determined. We used regression, adjusted for educational level, cardiovascular factors, and lifestyle factors, to test whether cross-sectional associations between biomarkers and cognitive performance and structural brain changes were modified by age (<60 versus ≥60 years). ≥60 years, higher NT-proBNP was associated with lower memory (β [SD] per 10-fold higher level [95% confidence interval (CI)], −0.11 [−0.22 to −0.00]), information processing speed (−0.12 [95% CI, −0.21 to −0.03]), executive functioning (−0.12 [95% CI, −0.22 to −0.03]), and smaller GM (β [mL] per 10-fold higher level, −6.89 [95% CI, −11.58 to −2.20]). Additionally, higher cTNT was associated with lower memory (−0.33 [95% CI, −0.53 to −0.12]) and information processing speed (−0.17 [95% CI, −0.3 to −0.01]); with smaller GM (−16.07 [95% CI, −24.90 to −7.24]) and greater WMH (10 β WMH per 10-fold higher level, 0.31 [95% CI, 0.10–0.52]). <60 years, NT-proBNP and cTNT were not associated with cognitive performance ( P interaction, <0.10). In contrast, higher NT-proBNP was associated with smaller GM (−7.43 [95% CI, −11.70 to −3.16]) and greater WMH (0.13 [95% CI, 0.01–0.25]; P interaction, >0.10). Higher cTNT was associated with greater WMH (0.18 [95% CI, −0.01 to 0.37]; P interaction, >0.10) but not with GM (0.07 [95% CI, −6.87 to 7.02]; P interaction, <0.10). Conclusions—: Biomarkers of cardiac injury are continuously associated with structural brain changes in both older and younger individuals but with poorer cognitive performance only in older individuals. These findings stress the continuous nature of the heart-brain axis in the development of cognitive impairment. Abstract : Supplemental Digital Content is available in the text.